2020
DOI: 10.1016/j.radcr.2019.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Internal iliac artery aneurysm embolization with direct percutaneous puncture and thrombin injection

Abstract: Endoleak it is the most common complication after endovascular abdominal aortic aneurysm repair and it represents the failure of endovascular treatment. In particular type 2 endoleak is associated with retrograde flow in the aneurysm sac from one or more arterial branches.We describe a reperfusion of the aortic aneurysm sac with slow-flow type II endoleak from the right internal iliac artery aneurysm through the posterior door previously closed with coils, and treatment with direct puncture of the internal ili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this case, ultrasound-guided local thrombin injection has the advantage of being a low cost, to guarantee the effectiveness of treatment, not needing sedation, less traumatic, technically simple procedure in experienced hands, paying highly attention to avoid non-target embolization [7] . Moreover, thrombin reduces significantly the presence of artifacts at the CT scan and gives us the exact extension of thrombosis into the aneurysm sac, while the ultrasound-guided offers the advantage of monitoring the progression of the thrombotic process induced by thrombin injection in real time [8] , without X-rays use.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, ultrasound-guided local thrombin injection has the advantage of being a low cost, to guarantee the effectiveness of treatment, not needing sedation, less traumatic, technically simple procedure in experienced hands, paying highly attention to avoid non-target embolization [7] . Moreover, thrombin reduces significantly the presence of artifacts at the CT scan and gives us the exact extension of thrombosis into the aneurysm sac, while the ultrasound-guided offers the advantage of monitoring the progression of the thrombotic process induced by thrombin injection in real time [8] , without X-rays use.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the elusive branching pattern of the IIA is invaluable for clinicians, especially gynecologists [3]. This knowledge is likely to prove essential during surgical procedures in which a certain part of the artery needs to be ligated in order to control pelvic hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that early diagnosis and early treatment are the most effective ways to reduce cancer mortality. Therefore, it is an urgent problem to be solved in the field of biomedicine to strive for new methods of early specific diagnosis of cancer [6]. There are many clinical diagnostic methods for tumors, and imaging is the most widely used clinical examination method.…”
Section: Introductionmentioning
confidence: 99%